Predictors of lower limb amputations in patients with diabetic foot ulcers presented in a tertiary care hospital of Pakistan - Ammar , Ahmed Siddique; Rizwan Khalid; Usman Malik; Misbah Zeb; Hafiz Muhammad Abbas; Shehr Bano Khattak (Journal of the Pakistan Medical Association, 2021)
Objective: The objective of this study is to assess the risk factors for lower extremity amputation in diabetic patients presented with diabetic foot ulcer. Methods: This is an observational study in a tertiary care hospital of Pakistan.135 patients of both genders having Type 1 or Type 2 diabetes and diabetic foot ulcer were selected through consecutive non probability sampling. The wounds of all the patients were assessed according to Wagner wound staging and wound sepsis was evaluated in terms of local infection of the wound, leukocytosis and osteomyelitis of the bone. The glycemic control of these patients were assessed on presentation by measuring HbA1c levels. All patients included in this study were undergone amputation which may be Ray amputation, below knee amputation and above knee amputation. Results: Majority of the patients belonged to the age group of 50 to 60 years, 35 male (25.9 %) and 24 female (17.77 %). Majority of the amputations were done in patients with Wagner stage 4 of wound classification, male 34 (41.46 %) and female 22 (41.50 %), patients with features of local wound infection, increased total leucocyte count and with bone showing features of osteomyelitis. Majority of amputations were done in patients with poor glycemic control on presentation, male 54 (65.85 %) and female 37 (69.81 %). Conclusion: With proper glycemic control and early presentation and treatment majority of amputations can be avoided in patients who develop foot ulcer due to diabetes. Keywords: Amputation, Diabetes, Osteomyelitis, Diabetic foot . Continuous...